Modification of deep breathing relaxation techniques on the osce participants’ anxiety level: a randomized control trial - Tia Nurhilmiah; Azhar Alamsyah; Dhinny Novryanthi (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Himpunan Perawat Medikal Bedah Indonesia (HIPMEBI), 2025)
Background: The final semester exam for students is a stressor that causes anxiety. The semester’s final exam can be theoretical and practice exams. The practice exam is an evaluation to know nursing students' skills before practicing in healthcare facilities. The method to evaluate students’ skills is Objective Structured Clinical Examination (OSCE) Purpose: To determine the effect of modified deep breathing relaxation techniques on the anxiety levels of (OSCE) participants through a randomized controlled trial design. Method: A randomized control trial of the parallel groups. The number of samples was 36 respondents. Data analysis using shapiro wilk, Levene test, paired t-test, independent t-test, and Cohen’s d. Results: the mean of anxiety decreased from 66.72 (3.2) to 53.72 (5.8) in the experimental group with a p-value is 0.000. On the other hand, the mean of anxiety increased from 43.17 (7.5) to 48.39 (9.3) in the control group with a p-value of 0.017. Additional data showed that the p-value of experimental vs control is 0.000, meaning there is a difference in score anxiety between the experimental and control group with an effect size is 0.5 (medium). Conclusion: A significant effect of modification of deep breathing relaxation on the anxiety level of students facing the OSCE exam. Keywords: Anxiety; Deep Breathing Relaxation Technique; Dzikr; OSCE.